2015
DOI: 10.2214/ajr.14.13820
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Nodules With Ground-Glass Opacity Can Be Reliably Measured With Low-Dose Techniques Regardless of Iterative Reconstruction: Results of a Phantom Study

Abstract: These results indicate that, if validated for other measurement tools and scanners, lung nodule volume measurements from scans acquired and reconstructed with significantly different acquisition and reconstruction techniques can be reliably compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
0
18
1
Order By: Relevance
“…At the same time, we wanted to provide some insight into any potential limit in the "measurability" of lung nodules, by stretching the range of dose protocols to as low as 0.3 mGy, the range of nodule sizes to 5 mm, and densities as low as −800 HU. Assessment was performed to quantify the accuracy and precision of volume estimates; both of these properties need to be within acceptable boundaries for a clinically useful biomarker (23). Our findings show that the volume of the 10 mm nodules of all densities was measured with both high accuracy (PB within 11%) and high precision (RC% within 5%).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…At the same time, we wanted to provide some insight into any potential limit in the "measurability" of lung nodules, by stretching the range of dose protocols to as low as 0.3 mGy, the range of nodule sizes to 5 mm, and densities as low as −800 HU. Assessment was performed to quantify the accuracy and precision of volume estimates; both of these properties need to be within acceptable boundaries for a clinically useful biomarker (23). Our findings show that the volume of the 10 mm nodules of all densities was measured with both high accuracy (PB within 11%) and high precision (RC% within 5%).…”
Section: Discussionmentioning
confidence: 85%
“…We limited our review of related work to phantom studies, which enable the analysis of both accuracy and precision due to the availability of a reference standard regarding nodule size and allow the acquisition of multiple repeated scans without concern to patient exposure. Li et al (6), Doo et al (22), and Siegelman et al (23) examined the volumetry of low-density nodules across different imaging protocols, but the lowest nodule density was limited to −630 HU. Scholten et al (18) and Linning et al (24) did not examine the effect of different reconstruction methods beyond FBP.…”
Section: Introductionmentioning
confidence: 99%
“…23 Doo et al 23 showed that IR significantly improved the accuracy of lung nodule volumetry in low-dose CT compared with FBP, particularly for ground-glass nodules (2630 HU). Also, Siegelmann et al 24 in a recent work state that pulmonary nodules with groundglass opacity can be reliably measured with low-dose techniques down to a CTDI vol of 0.8 mGy regardless of IR. Willemink et al 25 found that with IR no clinically significant differences between lung nodule volumes are evident.…”
Section: Discussionmentioning
confidence: 99%
“…A larger number of results derived from studies using newer generation scanners did not confirm the previous observations. Indeed, the introduction of iterative reconstructions, employed to increase image quality in favour of a further reduction of the effective radiation dose, demonstrated an even better performance compared to that of the traditionally used filtered-back projection reconstructions [101][102][103][104][105][106][107][108][109][110][111][112].…”
Section: Factors Influencing Nodule Measurement Variationsmentioning
confidence: 99%